Aplikasi Metode Value Engineering dalam Penentuan Alternatif Fasilitas Rumah di Perumahan - Mas'udin, Ilyas (Department Industrial Engineering, University of Muhammadiyah Malang, 2001)
Every Real Estate Developer want the houser built wanted by customers. There is a dicrease in sale of houses that be saled by Tegalgondo Asri developer caused customer's unsatisfaction in fasilities or import of sevise value given by developer to customers who lived there. One of alternative to rise design value vasilities is making a new fasility design better than the old one.